Quest Back about The Integrity of Incumbent Regional Head to be Nominee in Different Region - Charlyna S Purba; Joko Martono; Rini Setiawati (International Journal of Multi Discipline Science, 2018)
Regional head and vice regional head are selected to be a leader in Indonesian region as Indonesian Local Government Law. In their campaign, they promote their visions, missions, and work program if they were selected as regional head and vice regional head. In fact, they nominate and nominated to be a regional head candidate and vice regional head candidate in the same region and even different region for the next election before they were able to prove their integrity in their promises. Whereas, their integrity is a guarantee for democratic goals to local autonomy implementation the region got. It caused by the legal vacuum as found in this issue. The study recommends a legislation revision for Article 7 of 10th Governor, Regent, and Mayor Election Law of 2016, the pairs of regional head candidate requirement should have a specific provision that the newly elected regional head an/or vice regional head cannot be a nominee as regional head candidate and/or vice regional head candidate before their length of service is finished.